Tô Hân
0
0
Câu hỏi:
Câu trả lời của bạn: 13:45 16/09/2021
Câu hỏi:
Câu trả lời của bạn: 13:30 16/09/2021
Câu trả lời của bạn: 13:35 16/09/2021
Câu hỏi:
Câu trả lời của bạn: 13:26 16/09/2021
Câu hỏi:
Câu trả lời của bạn: 10:31 16/09/2021
Câu hỏi:
Câu trả lời của bạn: 10:31 16/09/2021
Câu hỏi:
Câu trả lời của bạn: 09:38 16/09/2021
Câu hỏi:
Câu trả lời của bạn: 09:32 16/09/2021
Câu hỏi:
Câu trả lời của bạn: 09:33 16/09/2021
= (-x)^3 + 3 × (-x)^2 × 3+3×(-x)×3^2+3^3
=(3-x)^3
Câu hỏi:
Câu trả lời của bạn: 09:28 16/09/2021
= (-x)^3 + 3 × (-x)^2 × 3+3×(-x)×3^2+3^3
=(3-x)^3
Câu hỏi:
Câu trả lời của bạn: 09:04 16/09/2021
=-(x^2-10x+25)
=-(x-5)^2
Gửi bạn nhé